The relationship between managers’ emotional intelligence and human resource management effectiveness - AlGhanim, Munirah Ahmed AlJaser (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to investigate the impact of managers emotional intelligence of human resource on the academic training sector in the State of Kuwait. The descriptive-analytical method was used, and data were collected via a questionnaire distributed to members of the academic staff. The results revealed a high level of agreement among the sample regarding the presence of emotional intelligence (75%) and effective human resource management (72%) among academic managers. A strong positive correlation was found between emotional intelligence and HRM effectiveness. Statistical difference was found based on gender and educational qualification, while no significant differences were no age or years of experience. This study recommended developing comprehensive training programs focused on emotional intelligence, integrating training within the work environment, promoting healthy managerial relationships, encouraging open emotional expression, and adopting HRM practices that enhance employee satisfaction and organizational effectiveness.